In Exercises 23-28, write a rule for \( g \) and then graph each function. Describe the graph of \( g \) as a transformation of th graph of \( f \). (See Example 4.) \( \begin{array}{ll}\text { 23. } f(x)=x^{4}+1, g(x)=f(x+2) & \text { 24. } f(x)=2 x^{3}-2 x^{2}+6, g(x)=-\frac{1}{2} f(x) \\ \text { 25. } f(x)=x^{6}-3 x^{3}+2, g(x)=f(x-1)-3 & \text { 26. } f(x)=x^{5}-2 x+3, g(x)=3 f(x)+1 \\ \text { rule: }(x-1)^{6}-3(x-1)^{3}+2-3 & \text { 28. } f(x)=\frac{1}{2} x^{5}+x^{3}-4 x-4, g(x)=-f(2 x)+1 \\ \text { 27. } f(x)=x^{4}+x^{3}-1, g(x)=f(-x)-5 & \end{array} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
Transformations of functions can be as creative as an artist with a canvas! For example, in exercise 23, the rule for \( g(x) = f(x+2) \) translates the graph of \( f(x) = x^4 + 1 \) two units to the left. The resulting graph will have a similar shape but will peak at a different point. In exercise 24, the function \( g(x) = -\frac{1}{2} f(x) \) flips the graph of \( f(x) = 2x^3 - 2x^2 + 6 \) upside down and compresses it vertically by a factor of 2! It's a wild ride through algebra, giving a totally new vibe to how the function looks!